Lagrangian Study on Critical Structures During Streamwise Vortex Generation in Open Cavity Flows - Chen, Zhizhe; Luo, Yong; Han, Shuaibin; Zhang, Jiazhong; Zhang, Shuhai; Fan, Shicheng; Cheng, Yulin; Xu, Feng; Ding, Wei (Journal of Environmental Accounting and Management, 2026)
Finite-time Lyapunov exponent (FTLE) is introduced to study the evolution of streamwise vortices in a cavity flow, which is crucial in the mass exchange and pollutant emission around aircrafts. First, the structures of streamwise vortices are captured using ridges of FTLE, and the evolution of streamwise vortex structures is illustrated in detail. The results show that there exists asymmetry featured by differences in structure and scale between streamwise vortices. Then, the evolution of vortex structures is analyzed and compared. It is found that several critical flow structures inside the cavity could block the forming of certain vortex, causing differences in evolution of vortex structures. Such flow structures are then briefly introduced and studied. Finally, the influences of asymmetry of the flow on streamwise vortex formation are summarized. In conclusion, the differences in flow structures imply that critical flow structures have strong influences on the formation of streamwise vortices, which could serve as a main mean of mass transport across the shear layer. The results provide theoretical support for controlling mass transport and thus reduce pollutant emission through cavity structures.